Community interventions improving mental health in minority ethnic adults in the UK: a scoping review. (30th September 2020) - Baskin, C; Zijlstra, G; McGrath, M; Lee, C; Duncan, F; Oliver, E; Osborn, D; Dykxhoorn, J; Kaner, E; Gnani, S
Abstract: Background: Black, Asian and Minority Ethnic (BAME) groups in the UK are disproportionately affected by poor mental health. This scoping review sought to determine the effectiveness of community interventions designed to improve the metal health and wellbeing of adults from BAME groups in the UK. Methods: We searched six electronic academic databases for studies published between 1990- 2019. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist and the Template for Intervention description and replication (TIDieR) guide was used for data extraction and intervention descriptions. Quality was assessed using Cochrane Risk of Bias tools. Grey literature results were deemed beyond the scope of this review; numerous (>50) small scale community interventions were found without available outcomes data. Results: Of 4, 501 studies, seven met the inclusion criteria: four randomised control trials, one pre and post pilot study, one cross sectional study and one ethnographic study. Interventions included therapy-style sessions, peer-support groups, educational materials, gym access, and a family services programme. Common components included a focus on tackling social isolation, using lay health workers from within the community, signposting, and cultural adaptation. Only three studies reported a statistically significant positive outcome on mental health and six were appraised as having a high risk of bias. Knowledge gaps emerged around effective interventions for men, some BAME groups, and tackling the wider determinants of mental health. Conclusions: There is a paucity of high-quality evidence on community interventions focussed on improving public mental health among BAME groups. Decision makers need scientific evidence to inform effective approaches to mitigating health disparities. Our next steps are to map promising community activities and interventions that are currently being provided to help identify emerging evidence. Key messages: Evidence is limited and weak on community interventions that reduce mental health burden among minority ethnic people. Evaluation of promising interventions at scale can close the evidence gap.